Study of Emotional Dissonance and Service Delivery among the Employees of Banking Sector: A Mediating Effect of Emotional Intelligence and Moderating Effect of E- Banking - Sabiq, Akhtiar Hussain; Mangi, Qamar Abbas; Soomro, Hassan Jawad; Rajper, Zulfiqar Ali; Khaskheli, Ghulam Akbar (International Journal of Psychosocial Rehabilitation, 2020)
Scope: In service industries, most of the organizations many organizations are now understanding that service delivery is the key component to satisfy customer needs and wants. Organization success is depending upon customer satisfaction and equally important to customers as well as employees. Objectives: Banks, as one of the most important financial intermediaries, provide the necessary channel through which savings may be utilized as investments. Thus, the role of banks and bankers in economic development of a country cannot be undermined. Banking sector employees are facing a lot of psychological problems at workplace; these problems are associated with their emotions and attitudes. In workplace, bankers are involved delivering service to customers for this they are emotionally involved and hide their actual emotions to fulfil the emotional requirement of their job. The difference between actual and emotions and expressed emotions is called as emotional dissonance (ED). In this situation, the role of emotional intelligence (EI) as mediator and E Baking as moderator also investigated. Method: A descriptive quantitative research design has been used; data collected through adopted and modified questionnaires; data has been analyzed in SPSS v20, AMOS v 20.CFA. Path analysis techniques have been applied and hypothesis tested. For mediation analysis Baron and Kenny (1984) was used. Results: Results indicated that emotional dissonance has significant negative impact on service delivery. More over emotional intelligence mediates the relationship between emotional dissonance and service delivery (SD) and reduces the negative impact of (ED) on service delivery. At last, E- banking moderates the relationship between (ED) and (SD).